Optical absorption signature of a self-assembled dye monolayer on graphene - Sghaier, Tessnim; Le Liepvre, Sylvain; Fiorini, Céline; Douillard, Ludovic; Charra, Fabrice (Beilstein Journal of Nanotechnology, 2016)
A well-organized monolayer of alkylated perylene-3,4,9,10-tetracarboxylic-3,4,9,10-diimide (PTCDI) has been formed onto CVD graphene transferred on a transparent substrate. Its structure has been probed by scanning tunnelling microscopy and its optical properties by polarized transmission spectroscopy at varying incidence. The results show that the transition dipoles of adsorbed PTCDI are all oriented parallel to the substrate. The maximum absorption is consistent with the measured surface density of molecules and their absorption cross section. The spectrum presents mainly a large red-shift of the absorption line compared with the free molecules dispersed in solution, whereas the relative strengths of the vibronic structures are preserved. These changes are attributed to non-resonant interactions with the graphene layer and the neighbouring molecules.
Keywords: absorption spectroscopy; dye aggregates; graphene; molecular monolayer; optical spectroscopy; perylene-3,4,9,10-tetracarboxylic-3,4,9,10-diimide (PTCDI); scanning tunnelling microscopy; self-assembly; self-organization